2011
DOI: 10.1002/hep.24125
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-492 Is Processed From the Keratin 19 Gene and Up-Regulated in Metastatic Hepatoblastoma σ

Abstract: MicroRNAs (miRNAs) are well-known regulators of proliferation, apoptosis, and differentiation and are recognized to play an important role in the development of cancers. Here we aimed to identify the functional contribution of miRNAs to the biology of hepatoblastoma (HB), the most common malignant liver tumor in childhood. As overexpression of the oncogene PLAG1 (pleomorphic adenoma gene 1) is a characteristic phenomenon in HB, we used RNA interference and subsequent miRNA array analysis to identify miR-492 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 38 publications
0
62
1
Order By: Relevance
“…Increasing evidences indicate that miR-492 has been shown to be one of the important determinants of cell tumorigenicity in multiple cancers [9][10][11]. However, the relationship between breast cancer and the expression of miR-492 has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences indicate that miR-492 has been shown to be one of the important determinants of cell tumorigenicity in multiple cancers [9][10][11]. However, the relationship between breast cancer and the expression of miR-492 has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…They guide the association of the RNA‐induced silencing complex with target messenger RNAs (mRNAs), mostly through interactions with the 3′‐untranslated region (UTR), resulting in translational repression and/or mRNA destabilization 11, 12. Deregulation of miRNA biogenesis and expression is a hallmark of cancer12 and has been reported in HBL 13, 14, 15. Unlike small interfering RNAs (siRNAs), miRNAs can simultaneously target multiple genes involved in the same cellular pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed both consistent and inconsistent results regarding the correlation between miR-492 and the development of gastrointestinal cancers. It was reported that miR-492 could originate from the coding sequence of the hepatoblastoma marker gene keratin 19 (KRT19) and miR-492 along with its associated targets might serve as new hepatoblastoma biomarkers of clinical utility and could assist to explore targeted therapies, especially in metastatic hepatoblastoma with a poor prognosis [19]. However, there was an inconsistent report describing that the gene polymorphisms of miR-27a, miR-146a, miR-196a-2, miR-492, miR-492a and miR-608 were not associated with the presence of colon cancer in European subjects [20].…”
Section: Discussionmentioning
confidence: 99%